Knockdown of APOPT1/COA8 Causes Cytochrome c Oxidase Deficiency, Neuromuscular Impairment, and Reduced Resistance to Oxidative Stress in Drosophila melanogaster - Brischigliaro, Michele; Corrà, Samantha; Tregnago, Claudia; Fernandez-Vizarra, Erika; Zeviani, Massimo; Costa, Rodolfo; De Pittà, Cristiano (Frontiers in Physiology, 2019)
Cytochrome c oxidase (COX) deficiency is the biochemical hallmark of several mitochondrial disorders, including subjects affected by mutations in apoptogenic-1 (APOPT1), recently renamed as COA8 (HGNC:20492). Loss-of-function mutations are responsible for a specific infantile or childhood-onset mitochondrial leukoencephalopathy with a chronic clinical course. Patients deficient in COA8 show specific COX deficiency with distinctive neuroimaging features, i.e. cavitating leukodystrophy. In human cells, COA8 is rapidly degraded by the ubiquitin-proteasome system, but oxidative stress stabilizes the protein, which is then involved in COX assembly, possibly by protecting the complex from oxidative damage. However, its precise function remains unknown. The CG14806 gene (dCOA8) is the Drosophila melanogaster ortholog of human COA8 encoding a highly conserved COA8 protein. We report that dCOA8 knockdown (KD) flies show locomotor defects, and other signs of neurological impairment, reduced COX enzymatic activity and reduced lifespan under oxidative stress conditions. Our data indicate that KD of dCOA8 in Drosophila phenocopies several features of the human disease, thus being a suitable model to characterize the molecular function/s of this protein in vivo and the pathogenic mechanisms associated with its defects.